PENERAPAN MODEL SQ3R PADA MPEMBELAJARAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SD - Purwaningsih, Dewi; Heru Purnomo (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine the effectiveness of the implementation of the SQ3R learning model in improving the ability of grade III elementary school students in solving mathematics problems. By using a qualitative approach and case study design, an in-depth picture of students' perceptions and experiences during the learning process was obtained. The results show that the SQ3R learning strategy helps students understand and analyze problems in a more structured way, thus having an impact on improving their ability to solve problems. This study contributes to the development of innovative and effective learning methods, and can be used as a reference by teachers and researchers in designing learning approaches that support improving students' academic achievement.